Is Loneliness Associated With Celebrity Attraction in LGBT+ Persons?. Issue 14 (6th December 2022) - McCutcheon, Lynn E.; Reyes, Marc Eric S.; Zsila, Ágnes; Huynh, Ho Phi
ABSTRACT: The present study is a conceptual replication of the functional alternative hypothesis, which states that when it is difficult for some persons to form satisfactory interpersonal relationships they turn to parasocial relationships as a functional alternative. In this study, the Celebrity Attitude Scale (CAS), a one-item measure of interest in celebrities in general, the Five-item Adaptation of the Revised UCLA Loneliness Scale (FALS), and the Receiving Emotional Support Subscale (RESS) were administered to 222 self-identified LGBT+ and 436 self-identified heterosexual persons from the Philippines aged 18 to 77 years old. We hypothesized that sexual orientation would moderate the relationship between loneliness and celebrity worship, such that the association between loneliness and celebrity worship would be stronger among LGBT+ individuals than among heterosexual individuals. This hypothesis was confirmed when the target person was one's favorite celebrity. Second, we hypothesized that lower levels of perceived social support among LGBT+ Filipinos would be associated with a stronger correlation between loneliness and celebrity worship as compared to LGBT+ Filipinos with a higher level of social support. Third, we hypothesized that younger LGBT+ persons would have a stronger association between loneliness and celebrity worship as compared to older LGBT+ persons. Results failed to confirm the social support and age hypotheses. The findings and limitations were discussed, and suggestions for further research were noted.